FACTORS RELATED TO ANEMIA IN PREGNANT WOMEN EVENTS IN GENERAL HOSPITAL REGIONAL dr. ZAINOEL ABIDIN - Faradilla Safitri; Mizan Jalinan (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Anemia is a common blood disorder that occurs when levels of red bloodcells in the body becomes too low. Data from Riskesdas the year 2013 thenumber of pregnant women suffer from anemia as much as 37.1%, this isvery different to the incidence of anemia among pregnant women in theDistrict General Hospital dr. Zainoel Abidin with a very low percentage of2.9% to 3.4%. To analyze the relationship between age, parity, education,occupation, gestational age, origin of a referral, and health servicesResearch methodsThis type of research is analytic survey using casecontrol design. Univariate analysis found women with anemia 33.3% andanemia not as much as 66.7%. Bivariate analysis between age <20 yearswith anemia (p = 0.001, OR = 9.549), parity (p = 0.001, OR = 1.955),gestational age (p = 0.027, OR = 1.608), education (p = 0.002, OR =2.338), occupation (p = 0.006, OR = 2.167). Results of multivariateanalysis the dominant variable is the age of the OR (age> 35 years =9.009 and aged <20 years = 6.994). No correlation between age, parity,gestational age, education, work with anemia among pregnant women. allpregnant women at risk for anemia, pregnant women should routinely visitantenatal care, because the mother will get information about thenutritional needs during pregnancy and other factors that can lead toanemia during pregnancy.Keywords: Anemia, age, education, gestational age, parity